Peer Instruction In A Flipped Learning Environment: Examining ESL Students’ Participation In Writing Argumentative Essays - Amreet Kaur Jageer Singh (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
Over the years, peer instruction and flipped learning approach has indicated its usefulness in teaching and learning. However, studies on how peer instruction in a flipped learning environment encourage active student participation in writing remain limited in Malaysia. Therefore, this study examines ESL students' participation during peer instruction in the flipped learning environment when composing argumentative essays. A total of 120 upper intermediate students undergoing an English proficiency course at a teacher education institution in Malaysia participated in this study. Qualitative data were gathered from student assessment forms (pair work and group work), lesson study logs, EdPuzzle video quizzes, and samples of student worksheets. Descriptive interpretations and thematic analysis were used to analyse textual data. The findings revealed that ESL students participated in this study by engaging themselves in interactions during in-class writing activities, contributing knowledge to others, getting prepared with the essential concepts and content before class, focusing on the task, and assessing the quality of argumentative writing. The findings implicate that teachers should consider the use of peer instruction in a flipped learning environment for students to engage actively in the teaching and learning of argumentative essay writing.